Pengembangan Instrumen Penilaian Pembelajaran Berbasis Wordwall pada Materi Mengulas Karya Fiksi di Kelas VIII SMP Swasta Kristen Tomosa I - Gulo, Desniat Hardianti; Nrudru, Mastawati; Bu'ulolo, Yanida; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2026)
The assessment of Indonesian language learning in the "Reviewing Fiction" topic in eighth-grade students at Tomosa 1 Christian Middle School still uses less interactive instruments, thus suboptimal student engagement in the evaluation process. This situation has prompted the development of more engaging and user-friendly digital assessment instruments. This study aims to develop a Wordwall-based learning assessment instrument on the material Reviewing Fiction Works for class VIII students of SMP Kristen Tomosa 1. The study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, questionnaires, and validation by material experts, media experts, and learning practitioners to assess the feasibility of the developed product. The research product is a Wordwall-based assessment instrument designed to make the evaluation process more interactive, interesting, and easily accessible to teachers and students. The development results show that the resulting instrument meets the feasibility criteria based on the assessment of validators so that it is suitable for use as a learning evaluation medium. The development of this instrument provides an alternative digital assessment that can support the implementation of Indonesian language learning evaluations in a more innovative manner, increase student engagement, and make it easier for teachers to carry out the assessment process.